RISK MANAGEMENT OF DUE TO EXPOSURE TO PESTICIDE POISONING FOR TOBACCO FARMERS IN THE JEMBER DISTRICT - Eri Witcahyo; Isa Ma’rufi (UNEJ e-Proceeding)
The main problem is the use of pesticides at thistime when farmers use pesticides and not on thebasis of necessity be indicative, but carried out"blanket cover system", it means there is not a plantpest or noxious poison that is constantly sprayed toplant. Besides spraying technique is sometimesdownwind, causing farmers unknowingly inhalepesticides. Excessive pesticide use behavior as itactually causes new problems that their pesticideresidues in agricultural products, and ultimatelyharm the farmers and the wider community both hissafety and health (MOH, 2006).The issue of pesticide use also occurs in tobaccofarmers in Jember district, most of the farmers donot pay attention to the rules of the use of pesticidesand the use of PPE is not standardized so it is veryrisky to poisoning by pesticides. Jember is one of themajor tobacco-producing areas in Indonesia. Typesof tobacco grown in this region are the na-OogstBesuki tobacco. Besides to its rich aroma, this type oftobacco were famous because of its elastic so it isfitting to be a cigar wrapper. That's what makes thistobacco known in international marketPesticides are chemical substances that are used formaterial used to control, reject, lure, or eradicatepests. Pesticides have a major role in increasingagricultural production. Based on the experience inLatin America with the use of pesticides can increaseproduction up to 40% on cocoa. In Pakistan,pesticides help increase sugarcane production by33%, and based on the record FAO pesticide use cansave 50% on the results of the cotton plant (Sudomo,1992; Mahyuni, 2015)In agriculture, use of pesticides has been perceivedbenefits to increase production. The presence ofpesticides benefits and advantages such as rapidreduce the population of pests of plants with alonger period of control, easy and practical to use it,easily manufactured on a large scale and easilytransported and stored. It was economical beneficialin use of pesticides. However, that does not meanthe use of pesticides does not cause adverse effects.Pesticides enter the body through the skin,absorption through the skin continue for pesticidesstill in the skin, through the mouth (ingestion) due toaccident, negligence or intentional (suicide) wouldresult in severe poisoning and death, throughbreathing can be a powder, droplets or steam cancause serious damage to the nose, through thethroat if inhaled quite a lot. Then through bloodcirculation can finally get into the organssystematically. Organs are usually exposed to toxinsare the lungs, liver (hepatic), central nervous system(brain and spinal cord), bone marrow, kidneys, skin,nervous edge, and blood. The toxic effects on thebody also will give local effects such as irritation,allergic reactions, dermatitis, ulcers, acne and othersymptoms (Ekti, 2007).Manifestations class organophosphate pesticidepoisoning occurs in various organs in the body. Mildsymptoms that often arises is dizziness, blurredvision, hyper saliva, nausea, vomiting, diarrhea, andeven can cause severe bronchospasm andrespiratory muscle paralysis with manifestations ofshortness of breath, as well as abnormalities in theheart, namely the occurrence of cardiac arrhythmias.On acute exposure, class of organophosphatepesticides can cause respiratory problems.Disruption of the respiratory center will cause asymptom that leads to the progressive bradipneubreathing. Health problems occur due to the doseand frequency that do not fit. As an example, a doseof 1 ml of pesticides with high value activeingredients used for 1 ha of crops, farmers usepesticides in their application for theorganophosphate class of ½ ha with a reason topests or plant pests (OPT) that attack die soon. Thefrequency of spraying more than 3 times a month isnot good for health and the standard pesticidespraying (Arifiyanto, 2008).Risk analysis is a process consisting of the steps thathave been formulated, having the sequence (steps)and assist in making better decisions by looking atthe risks and impacts that may occur. Riskmanagement is a systematic method that consists ofProceeding ICMHS 2016 ISBN 978-602-60569-3-1205establishing the context, identifying, researching,evaluating, treatment, monitoring andcommunicating risks associated with any activity,process or function so as to minimize losses of thecompany (AS / NZS 4360; 2004).The process of risk analysis as contained in the RiskManagement Standard AS / NZS 4360, which include(1) Communication and consultation, risk analysisneeds to be communicated to all parties.Communication used may be circular, practicalguidance, communication forums, handbooks orguidelines; (2) define the context (purpose), thisprocess takes place within the framework of theorganization's strategic, organizational and riskmanagement context; (3) Risk identification, thisstep seeks to identify risks to be managed, should beusing a good system. Risk identification shouldinclude either exists or does not exist in theorganization; (4) Risk analysis, aiming to separatesmall and large risks and provide the data evaluationand improvement; (5) Risk evaluation, is to evaluatethe risks if those risks are acceptable or not, (6) Riskmanagement is the realization of a risk managementefforts workplace.The objective of this study was to analyze the risk ofpesticide poisoning in the tobacco farmers inJember.